Чужая беда: повести, рассказы : перевод с чувашского / М. Кибек - Кибек Митри (Советский писатель, 1965)
Экземпляры: КХ (20190207) / Инвентарный номер: 389063 / Сис.шифр: С(Чув) / Авт.знак: К 38 / ГРНТИ: 17 / ББК: 84(2)